"School of hard knocks" – what can mental health researchers learn from the COVID‐19 crisis?. (24th December 2020) - Sonuga‐Barke, Edmund J.S.
Abstract : Since the COVID‐19 pandemic took hold in the first quarter of 2020, children and their families across the world have experienced extraordinary changes to the way they live their lives – creating enormous practical and psychological challenges for them at many levels. While some of these effects are directly linked to COVID‐related morbidity and mortality, many are indirect – due rather to governmental public health responses designed to slow the spread of infection and minimise the numbers of deaths. These have often involved aggressive programmes of social distancing and quarantine, including extended periods of national social and economic lockdown, unprecedented in the modern age. Debates about the appropriateness of these measures have often referenced their potentially negative impact on people's mental health and well‐being – impacts which both opponents and advocates appear to accept as being inevitable.